A General Inequality for CR-Warped Products in Generalized Sasakian Space Form and Its Applications - Yanlin Li; Akram Ali; Rifaqat Ali (Advances in Mathematical Physics)
In the present paper, by considering the Gauss equation in place of the Codazzi equation, we derive new optimal inequality for the second fundamental form of CR-warped product submanifolds into a generalized Sasakian space form. Moreover, the inequality generalizes some inequalities for various ambient space forms.